Combined Hamartoma of the Retina and Retinal Pigment Epithelium (CHR-RPE) in a Baby - MD, Mariana Sgroi; MD, Franco Benvenuto; MD, Francisco Maldonado; MD, Luis Diaz Gonzalez; MD, Carlos Rugilo; MD, Adriana Fandiño (Journal of Ophthalmology and Research, 2021)
Combined hamartoma of the retina and retinal pigment epithelium (RPE) is a rare, congenital, and benign tumour that may be mistaken with a choroid melanoma or retinoblastoma. These tumours often show an epiretinal membrane, tangential traction, disorganization of the retinal layers, and underlying uniform choroidal thinning. Our case report aims to describe the clinic and its correlation with MRI imaging on the evolution of a combined hamartoma of the retina and retinal pigment epithelium in a 5-month-old baby with six years of follow up.